PEROLEHAN BELAJAR SISWA KELAS III DENGAN MODEL PEMBELAJARAN WORD SQUARE PADA MATA PELAJARAN PKn DI SD NEGERI BESANI KABUPATEN BATANG - Dyah Ayu Rofiah (Universitas Negeri Makassar, 2018)
This research is motivated by PKn learning, students' interested and motivation were very lacking. Especially in the matter of the importance of self-esteem, many students can not understand the importance of self-esteem. There are several things that can cause student learning interest to diminish, for example because when students start asking questions or making opinions sometimes there were others who mocking, there are also students who have quiet nature, and students also have different learning styles so that learning outcomes are less than optimal, KKM (Minimum Completion Criteria) for PKn lessons at SD Besani Kabupaten Batang, which is 70. The formulation of the problem is whether the word square learning model has a significant effect on PKn learning outcomes of third grade students of SD Negeri Besani Kabupaten Batang. The research hypothesis is the word square learning model can have a significant effect on the learning outcomes of PKn class III SD Negeri Besani Kabupaten Batang. The purpose of the study was to determine the effect of word square learning model on PKn learning outcomes of third grade students of SD Negeri Besani Kabupaten Batang. This type of research is quantitative through experimental research method. True experimental design research is designed with posttest-only control design. The population was students of SD Negeri Besani Kabupaten Batang, the samples were all third grade students and the sampling technique used was non probability sampling with saturated sampling types. The data analysis technique used is the data requirements test that is the normality test using he Liliefors test and testing the hypothesis using a two sample t-test. t. The results of statistical analysis with t-test obtained 2.13 and with a significance level of 5% of 0.2149, so that it was accepted. So, it was concluded that the word square learning model affected the learning outcomes of third grade students of SD Negeri Besani Kabupaten Batang. The advice that researchers can convey to elementary school teachers is that learning by using word square learning models can be implemented in the teaching and learning process as a variation of teaching so that it is not monotonous and creates creativity in students and confident in learning.